MEASUREMENT OF BRAIN TUMOR VOLUME USING THE ACTIVE CONTOUR METHOD (Jurnal Ipteks Terapan, 2024)
This research discusses the importance of developing digital image processing programs to support brain tumor detection via CT-Scan. Manual identification by radiologists can result in errors and inaccuracies in measuring tumor volume. Therefore, this study proposes the application of the active contour method as an alternative that can automatically segment brain tumors and calculate their volume with high accuracy. This method is expected to overcome challenges in medical image analysis, provide efficient solutions, and help improve diagnostics through a reliable automated approach. The experimental results show the potential of the active contour method in increasing the accuracy and efficiency of brain tumor identification, making it a valuable contribution to the development of technology in the field of medical radiology.